Plate wastage among hospitalized cancer patients - Abu Zaid, Zalina; Lim, Vivien Chiau Chiann; Jamhuri, Norshariza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Plate wastage in hospital contributes to malnutrition-related complications including longer hospitalization among cancer patients. The objective of this study was to determine the relationship between patients’ experiences of access to food hospital and plate wastage among hospitalized cancer patients. Methods: Two hundred and thirty-one cancer patients in the National Cancer Institute, Malaysia were recruited for this study. All eligible patients were undergoing cancer treatments and provided with informed consent. Data obtained included socio-demographic characteristics and patients’ experiences of access to food hospital which will contribute to plate wastage. Plate wastage was determined by weighing the unwanted food left on the plate. Results: Prevalence of plate wastage among cancer patients was high at approximately 54%. The appearance of food served was associated with higher plate wastage (p<0.01). Conclusion: This finding shows that the prevalence of plate wastage was high which may inhibit food consumption and affecting nutritional status among cancer patients with oncologic treatment. Effective strategies that address factors associated with plate wastage should be taken among hospitalized cancer patients.